2006
DOI: 10.1038/sj.ejcn.1602536
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices and associated factors among children under 24 months of age in Timor-Leste

Abstract: Objective: To describe breastfeeding practices and to assess the sociodemographic factors associated with selected breastfeeding indicators. Design and setting: The 2003 Demographic and Health Survey was a multi-stage cluster sample survey of 4320 households from four different geographic areas in Timor-Leste. Subjects: A total of 2162 children aged 0-23 months. Results: A high proportion (97.6%) of infants had been ever breastfed, but only 46.1% had initiated breastfeeding within the first hour of birth. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
6
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 20 publications
8
36
6
4
Order By: Relevance
“…Another study also showed that only 23% of urban mothers breastfed their children up to 4 months and it declined to 16% at 6 months. 10 Talukder et al 11 also showed that only 66% of the urban elite exclusively breastfed their children at birth, 42% at one month and 12% at fourth month. This study found that exclusive breastfeeding was more common among multiparous mothers.…”
Section: Discussionmentioning
confidence: 97%
“…Another study also showed that only 23% of urban mothers breastfed their children up to 4 months and it declined to 16% at 6 months. 10 Talukder et al 11 also showed that only 66% of the urban elite exclusively breastfed their children at birth, 42% at one month and 12% at fourth month. This study found that exclusive breastfeeding was more common among multiparous mothers.…”
Section: Discussionmentioning
confidence: 97%
“…This result is higher when compared to the 2011 Ethiopian DHS report 51.5 % [7] and from studies done in; Saudi Arabia 22 % [10], Raya Kobo Northwest Ethiopia 71.7 % [11], Goba district Southeast Ethiopia 52.4 % [12], Arba Minch zuria southern Ethiopia 57.6 % [13], India 36.4 % [14], 34 % among those who deliver their child through vagina in Harcourt teaching hospital [15], Nepal 66.4 % [16], in a study using 2011 EDHS 52 % [17], Tanzania 51 % [18], Timor Liste 46.1 % [19], in Lebanon 55.9 % [20], in hospital delivered infants India 36.4 % [21], in baby friendly hospitals in Turkey 35.2 % [22]. …”
Section: Discussionmentioning
confidence: 99%
“…has been shown to be positively associated with breastfeeding initiation and continuation in developed countries, an inverse relationship was found in developing countries [23,28,29]. Korean women who were college graduates or had a higher educational level were reported to have significantly lower breastfeeding rates compared to women with a lower educational status [14].…”
Section: Wwwkanorkrmentioning
confidence: 99%